Prediction of Pre-Compression Stress of Soil with Uniaxial Test (Agricultural Engineering, 2019)
The paper presents a concept of determination of pre-compression stress. It assumes that the stress value is close to the unit pressure value which is indispensable to increase the initial degree of soil compaction. Thus, an attempt was made to develop an empirical model for predicting the value of stress at which the initial compaction of a soil sample increases by a determined value. Samples with the so-called intact structure (NS) and soil material in the form of loose mass were collected from subsoil, and they were used to form model samples. Both types of samples were uniaxially compressed. For the study, data on moisture and dry bulk density of model samples were used, as well as determined ratios (conversion factors) that present relations between the results of compaction of model samples and samples with the intact structure. It was reported that the pressure necessary for the increase of the initial compaction of the model samples with the value of +0.05 or +0.10 g∙cm−3 were higher than the formation pressure respectively by 1.03-1.11 and 1.42-1.93 times. It was proved that for determination of the pre-compression stress of the NS samples models of linear regression for prediction the pressure needed to increase the initial compaction of the model sample by the value of +0.05 g∙cm−3, combined with a coefficient calculated for the present state of the soil properties, can be applied.